Meningkatkan Keaktifan Belajar Melalui Metode Permainan Mencari Kartu Pada Peserta Didik - Rahmah (JKPD (Jurnal Kajian Pendidikan Dasar), 2025)
Low student learning activity in the classroom often results from monotonous instructional strategies that fail to engage learners physically and mentally, creating a passive and unmotivated learning atmosphere. This study aims to improve student learning activity through the implementation of the card-finding game method as an enjoyable and interactive learning approach. This research employed a Classroom Action Research (CAR) design carried out in two cycles, following the stages of planning, action, observation, and reflection. The subjects of the study were 30 third-grade students of SDN Model Terpadu Madani, consisting of 19 boys and 11 girls. Data were collected through observation and analyzed using descriptive quantitative techniques to calculate student activity percentages based on observation sheets. The results showed a significant improvement in student learning activity from Cycle I to Cycle II, with an overall increase of 63.3%. Additionally, the number of students achieving the "active" category rose from only 16.7% in Cycle I to 80% in Cycle II. These findings indicate that the application of the card-finding game method effectively enhances student participation and learning activity in the classroom.